Guiding officers to deflect citizens to treatment: an examination of police department policies in Illinois - Jessica Reichert; Sharyn Adams; Jirka Taylor; Brandon del Pozo (BMC, 2023)
Abstract Background The U.S. overdose crisis has motivated police departments to enact policies allowing officers to directly deflect individuals to substance use disorder treatment and other services shown to reduce recidivism and subsequent overdose risk, as well as refer people who voluntarily present at police facilities with a desire for treatment. As a new way of operating, and one that relies on an officer's use of discretion for successful implementation, the practice benefits from guidance through written directives, training, and supervisory support. However, there is little information on the establishment, content, and execution of police department deflection policies, which hampers the implementation and dissemination of this promising practice. We analyzed 16 policies of Illinois police department deflection programs. Using content analysis methodology, we coded the policies for language and terminology, as well as program components and procedures. We aimed to examine how the policies were written, as well as the content intending to guide officers in their work. Results We found the policies and programs had notable differences in length, detail, terminology, and reading level. Only one policy mentioned the use of any type of addiction treatment medication, many used stigmatizing language (e.g., "abuse" and "addict"), and few mentioned "harm reduction" or training in the practice of deflection. Many policies restricted participation in deflection (i.e., no minors, outstanding warrants, current withdrawal symptoms), and critically, a majority of policies allowed police officers to exclude people from participation based on their own judgment. Conclusions We recommend police departments consider the readability of their policies and reduce barriers to deflection program participation to engage a larger pool of citizens in need of substance use disorder treatment. Since there is limited research on police policies generally, and the field of deflection is relatively new, this study offers insight into the content of different department policies and more specifically, how officers are directed to operate deflection programs.